Fool's Gold lives, loves, and misadventures in the Four Corners country - Schultheis, Rob (New York : Lyons Press, 2000)
The author describes his life in Telluride, while relating tales of local history and anecdotes concerning various inhabitants of the Four Corner region.
78113
Keywords: Schultheis, Rob; Country life -- Colorado -- Telluride; Country life -- Four Corners Region; Telluride (Colo.) -- Social life and customs; Four Corners Region -- Social life and customs; Telluride (Colo.) -- Biography; Four Corners Region -- Biography; Telluride (Colo.) -- Description and travel; Four Corners Region -- Description and travel